Ten-Year Experience of Chest Wall Reconstruction: Retrospective Review of a Titanium Plate MatrixRIB™ System - Wong, Teddy H. Y.; Siu, Ivan C. H.; Lo, Kareem K. N.; Tsang, Ethan Y. H.; Wan, Innes Y. P.; Lau, Rainbow W. H.; Chiu, T. W.; Ng, Calvin S. H. (Frontiers in Surgery, 2022)
Chest wall tumor resection can result in a large defect that poses a challenge in reconstruction in order to restoration chest wall contour, maintain respiratory mechanics and improve cosmesis. Titanium plates were first introduced for treatment of traumatic flail chest with promising results in restoring chest wall stability. Subsequently, the applications of titanium plates in chest wall reconstruction surgery were demonstrated in case reports and series. Our centre has adopted this technique for a decade and patients are actively followed up after the operation. We retrospectively analyze our 10-year-experience of using titanium plate and other reconstruction approaches for chest wall reconstruction, in terms of clinical outcomes, complications and reasons for reoperation to determine long term safety and efficacy. Thirty-eight patients who underwent chest wall resection and reconstruction surgery were identified. 11 had titanium plate insertion, 11 had patch repair or flap reconstruction and the remaining 16 had primary closure of defects. Chest wall reconstruction using titanium plate(s) and patch repair (with or without flap reconstruction) was associated with larger chest wall defects and more sternal resections than primary closure. Subgroup analysis also showed reconstruction by titanium plate technique was associated with larger chest wall defects than the patch repair or flap reconstruction (286.80cm2 v.s. 140.91cm2 (𝙥=0.083)). There was no 30-day hospital mortality. Post-operative arrhythmia was more commonly seen following chest wall reconstruction compared with primary closure (𝙥=0.041). Furthermore, more wound infections were detected following the use of titanium plate reconstruction compared with the patch repair (with or without flap reconstruction) approach (𝙥=0.027). In conclusion, the titanium plate system is a safe, effective and robust approach for chest wall reconstruction surgery, especially in tackling larger defect sizes.